Determinan Tax Avoidance Pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia - Heni Andani; Triyani Budyastuti (Politeknik Raflesia Press, 2025)
In Indonesia, tax avoidance still remains an issue. This research tends to analyze how sales growth, Firm size, and related party transactions affect tax avoidance. The focus of this study is mining companies on the Indonesia Stock Exchange (BEI). Purposive sampling was employed in this research, and 20 companies were observed from 2019 to 2023 using specified criteria. With the aid of Statistical Product and Service Solutions (SPSS) software version 25, the data analysis methods employed in this study include multiple regression testing, hypothesis testing, descriptive statistical testing, and traditional assumption testing.This research discovered that sales growth and firm size have a positive effect on tax avoidance. And the Related Party Transaction has no effect on tax avoidance.